The Role of Accountants in Facing Economic Digitalization Towards The Era of Society 5.0 - Salomi Jacomina Hehanussa (Green Publisher Indonesia, 2024)
In preparation for the era of Society 5.0, economic digitization has brought drastic changes that have triggered the evolution of the accounting profession. The Society 5.0 zone is seen as an area that encourages interaction between humans, technology and robots to improve the quality of life. Economic digitalization is a global phenomenon that is driving structural changes in the business and financial sectors. In the modern informatics era, technological advances have had a significant impact on accounting practices and strategic decision making by organizations. This research aims to track the development of economic digitalization and provide an overview of the important role of accountants in the context of Society 5.0. The results of this research show that the role of advanced accountants must be broad and flexible in order to participate in the digital revolution that is taking place. Competent and responsive accounting professionals will play a vital role in promoting national economic stability and competitiveness, as the country advances towards Society 5.0.